Measuring Attribute Of Product Of Vegetable Salad Of “Mamake” Micro Business Of Buddhist Community Group At Buddhi Vardhana Temple In Tangerang City - Sonny Santosa; Petrus T. Resi; Gregorius Widiyanto; Sutrisna Sutrisna (Primanomics : Jurnal Ekonomi & Bisnis, 2020)
This research is to measure product attributet of micro business vegetable salad “Mamake” in order to help Buddhist community group at Buddhi Vardhana Temple who have interest to run the same business. It needs a specific technique to identify the want and preference of consumer by measuring the utility and relative importance values of product attributes. This research uses conjoint analysis. Respondents of this research are 80 members of Buddhist community group at Buddhi Vardhana Temple. The analysis shows that the most preferred salad based on its importance level is vegetable salad chicken and cheese with importance value of 0,065, hence can be concluded that opening a micro business of vegetable salad “Mamake” of this type become a promising opportunity in micro business world